Techniques and tools of lean production: Multiple case studies in Brazilian agribusiness units - Satolo, Eduardo Guilherme [UNESP]; de Moura Hiraga, Laiz Eritiemi [UNESP]; Zoccal, Lucas Furlani [UNESP]; Goes, Gustavo Antiqueira [UNESP]; Lourenzani, Wagner Luiz [UNESP]; Perozini, Pedro Henrique [UNESP] (FapUNIFESP (SciELO), 2020)
The literature regarding Lean Production philosophy is vast depicting historical aspects, implementation challenges, benefits of its adoption and other topics applied to various industries and services. However, the agribusiness segment, one of the major segments of the global economy features a large gap in national and international literature. This article aims to conduct a research through multiple case studies concerning the use of techniques and tools of Lean Production System in agribusiness organizations. Multiple type case studies were conducted in eight agribusiness units from different segments through the application of structured interviews, on site visits and document analysis. The research carried has identified that Lean Production techniques and tools are applicable to agribusiness environments, and that the ones which involve improvements in process control, production flow and logistics have higher emphasis on research units. Techniques and tools such as long-term supplier and customer relationship, production smoothing/heijunka and value stream mapping distinguished themselves by the similarity of use when compared to previous studies in agribusiness environment. It was also identified that there are differences concerning the adoption of the techniques and tools in research units that operate in production environments of the type Make to Order or Make to Stock. Such differences are imposed by specificities that affect agribusiness organizations, which is indicative for future studies.
Técnicas e ferramentas do lean production: estudos de múltiplos casos em empresas do agronegócio brasileiro
Keywords: Agribusiness; Brazil; Lean manufacturing; Multiple case studies; Network analysis